Performance of the dominant bacterial species and microbial community in autotrophic denitrification coupled with iron cycle in immobilized systems. Issue 1 (15th April 2017) - Su, Jun feng; Cheng, Ce; Huang, Tinglin; Wei, Li
Abstract: We used three stable reactors to investigate the rates of nitrate removal coupled with iron cycle and the subsequent influence of the reaction on bacterial communities. The iron-reducing bacterium Klebsiella sp. FC61 was immobilized on the reactor columns of the experimental groups B (only Klebsiella ) and C ( Klebsiella  + magnetite). With the fluctuation of Fe 2 + to Fe3 + (iron cycle), the average nitrate removal efficiency increased from 73.22% to 93.91% and 86.92% to 97.84% in groups B and C, respectively, as the influent nitrate concentration decreased from 40 to 10 mg/L. However, the average rate of nitrate removal showed the opposite trend (from 2.08 mg/L/h to 0.67 mg/L/h and 2.41 mg/L/h to 0.69 mg/L/h in groups B and C, respectively) as the influent nitrate concentration decreased. Analysis of microbial distribution and community structures indicated that the population of Klebsiella sp. increased in groups B (from 18.21% to 41.21%) and C (from 25.43% to 46.80%) and contributed to the effective removal of nitrate in the reactors. Highlights: Autotrophic denitrification was achieved using immobilized systems coupled with iron cycle. A high average nitrate removal efficiency of 97.84% was obtained at low nitrate concentration. Magnetite addition aided the removal rate of nitrate. Klebsiella sp. FC61 was the dominant contributor for effective nitrate removal.